An insurance and investment portfolio model using chance constrained programming - Li, S.X. (Omega (Oxford), 1995)
An insurance and investment portfolio model is here formulated in terms of the ‘P-Models’ of Chance Constrained Programming, which is then related to the ‘satisficing concepts’ of Simon. For a given insurers' aspiration level of return on equity and risk levels of violating minimum requirements on return and on cash and liquid assets, we propose a method to maximize the insurers' probability of achieving their aspiration level, subject to two chance constraints and other regulatory and institutional constraints. An empirical example is given, based on the industry's aggregated data for a twenty year period.